Performance Effectiveness Analysis of KOTAKU Activity Management Unit in the Revolving Fund Loan Program in Tanjung Village, Labuhan Haji District, East Lombok Regency - Zakiro, Fadilla; Lestari, Baiq Anggun Hilendri; Suryantara, Adhitya Bayu; Ridhawati, Rini (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research aims to determine the effectiveness of the performance of UPK KOTAKU revolving fund loans in Tanjung Village, Labuhan Haji District, East Lombok Regency in 2022, as seen from Cost Coverage Ratio (CCr), Return On Investment (ROI), Portfolio at Risk (PAR), and Loan at Risk (LAR ), number of women's KSM members. Descriptive research method with a quantitative approach. The KSM research sample consisted of 38 KSM members and female KSM members. Data analysis involved gathering data in the field using CCr, ROI, PAR, LAR, and women's involvement. Research results: (1) Implementation of the UPK Amanah Tanjung revolving fund loan program is not effective; (2) Women's KSMs made loans to UPK Amanah Tanjung with a yield of 350%, indicating it was effective.